Pengaruh Tax Avoidance dan Corporate Governance Terhadap Nilai Perusahaan - Puspitasari, Aisyah Rahmadayanti Putri; Febriani, Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to examine the effect of tax avoidance and corporate governance on firm value in automotive sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data used in this research uses secondary data with the data collection method is purposive sampling which obtained data from 70 automotive sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data analysis used is an Econometric View which shows that tax avoidance with a regression coefficient of -0.165202 and a probability value of 0.0012 <0.05 has a significant effect in a positive direction on company value and corporate governance with a regression coefficient of 0.475325 and The probability value of 0.0136 <0.05 has a significant positive effect on company value. These results mean that the implementation of transparent, accountable and effective governance can be considered by stakeholders as a factor that increases company performance and value. So that healthy relationships between stakeholders and the company are important in achieving long-term growth and sustainability of the company.